Gerakan Peduli Literasi: Sinergi Mahasiswa, Duta Baca, dan Masyarakat untuk Pendidikan Anak di Desa Simanungkalit - Joy Ragil Sentana; Eldina Sarah Nababan (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The Literacy Care Movement Program is a form of community service by KPPM students implemented in Simanungkalit Village with the aim of increasing interest in reading and literacy culture among the community, especially elementary school children. This activity uses a qualitative research method with a case study approach, which focuses on the planning process, implementation, participation, and results and impacts of the program. The implementation of the program begins with coordination with village officials, site reviews, independent construction of Literacy Cottages, and socialization to partner schools. Various literacy activities are carried out interactively, including reading and writing classes, which are closed with a literacy competition as the peak of the event. The evaluation shows that the activities are effective and receive high enthusiasm from students, teachers, and the community. This program has succeeded in creating an alternative learning space and motivating the community to care more about the importance of literacy. In the future, the sustainability of the program needs to be maintained by involving the local community so that the spirit of literacy continues to grow and develop.